2009
DOI: 10.14742/ajet.1126
|View full text |Cite
|
Sign up to set email alerts
|

Case study of a computer based examination system

Abstract: <span>Electronic supported assessment or e-Assessment is a field of growing importance, but it has yet to make a significant impact in the Australian higher education sector (Byrnes &amp; Ellis, 2006). Current computer based assessment models focus on the assessment of knowledge rather than deeper understandings, using multiple choice type questions, and blocking access to more sophisticated software tools. This study explored a new system based on a customised version of an open source live CD, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 6 publications
(4 reference statements)
0
38
0
8
Order By: Relevance
“…Learners when tested on unfamiliar content, working under increased stress and cognitive load levels, may be disadvantaged when using computer-based tests as compared to traditional and more familiar paper-based assessments, unfairly affecting their performance. With regards to preference, prior positive experience with previous computer-based tests results in more positive attitudes to them (Fluck, Pullen & Harper, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Learners when tested on unfamiliar content, working under increased stress and cognitive load levels, may be disadvantaged when using computer-based tests as compared to traditional and more familiar paper-based assessments, unfairly affecting their performance. With regards to preference, prior positive experience with previous computer-based tests results in more positive attitudes to them (Fluck, Pullen & Harper, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…(Powers & O'Neill, 2006), assessed the degree of contribution of CBT to performance among a number of students of mathematics by using a questionnaire survey. It was found that no serious effect (12). Karadeniz (2009) studied the impact of CBT and PPT and mobile-based test on students' performance.…”
Section: Archives Of Business Research (Abr)mentioning
confidence: 99%
“…Der er i litteraturen beskrivelser af forskellige former for testsystemer, der kan anvendes ved digitale prøver -både kommercielt tilgaengelige systemer og systemer, som it--teknisk personale lokalt på bestemte uddannelsesinstitutioner selv har udviklet og afprøvet (Baumann et al, 2009;Ventouras et al, 2010;Stowell & Bennett, 2010;Fluck et al, 2009;Fluck et al, 2009;Costagliola et al 2007;Joglar et al, 2010;Marriott, 2009;Schmidt et al, 2009). Teknologimaessigt er fokus i litteraturen på testsystemer, der leverer randomiserede opgavesaet med MC--opgaver og lignende opgaver og spørgsmål til eksaminanderne og herefter automatisk bedømmer besvarelserne.…”
Section: Teknologiunclassified